Construção e validação de tecnologia educativa para acompanhantes durante o trabalho de parto e parto - Teles, Liana Mara Rocha (2011)
The present study aimed to build and validate a nursing educative technology (manual) directed for companions during labor and delivery. Methodological research developed in eleven stages. Begin, the five first regarding the construction of the manual, the following five referring to the validation process and, the last one, referring to the availability of the manual. The first stage corresponded to the content survey. In the second stage, there was a selection and written report of the raised content, in accordance with the demands of the companions. In the third stage, it was initiated textual elaboration. In the fourth stage, there was a raise of models, election and creation of 38 illustrations. The fifth stage corresponded to the layout of the manual, which was carried through according with the recommendations of the NBR6029 and developed through the program CorelDraw 15.0. After the five stages of construction of the educative manual, it was initiated the process of validation of the produced technology. In the sixth stage, nine specialists of the interest area were invited criteria in accordance with preset criteria (women’s health; obstetrics; technology in health; e instrument validation), which evaluated aims, structure and presentation, and relevance of the manual. A certain item was considered validated when it obtained a “Completely Adquetae” classification from at least half plus one of the number of specialists and Content Validity Index (CVI) higher or equal to 0,78. Some items were evaluated as satisfactory and others still need to suffer changes. As for the manual’s aim, specialists considered validated all questioned items, with an CVI between 0,88 and 1,0. As for structure and presentation of the manual, three items needed to adjust to the specialists suggestions: clarity and objectiveness of the messages; logic sequence of the content and match between writing and level of understanding of the target group. The CVI of the items that belong to this topic varied from 0,66 to 1,0. All items regarding the relevance of the manual were considered validated, with a CVI between 0,88 and 1,0. The global CVI of the educative manual was 0,94.. In the seventh stage, the educative manual was applied with eleven representatives of the target group obtained a level of conformity higher than 75% for the items evaluated such as organization, style of the writing, appearance and motivation of the manual. In the eighth stage, the alterations suggested from the specialists and representatives of the target group were accomplished: reformulating phrases, substitution of words or expressions; inclusion, substitution or relocation of information and illustration. The ninth stage corresponded to the review of the Portuguese by a specialized professional. In the tenth stage, the Flesch’s Index of Legibility was verified (FIL). The topics of the manual obtained a FIL between 50 and 94, which corresponds to an “Easy” or “Very Easy” reading, sufficient to a public with up to nine years of study. The last stage corresponded to printing of the manual. Finally, the educative manual validated by specialists and representatives of the target group is considered, regarding its appearance and content. Thus, further studies are necessary for the evaluation of the impact of this educative technology on the companion’s attitude in the labor room.